2022
DOI: 10.7759/cureus.29782
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio as an Early Predictor of Complication and Mortality Outcomes in Individuals With Acute Pancreatitis at a UK District General Hospital: A Retrospective Analysis

Abstract: The purpose of this study was to evaluate the predictive usefulness of the neutrophil-to-lymphocyte ratio (NLR) in patients with acute pancreatitis (AP) and establish a threshold for the prediction of poor outcomes. MethodsFor this investigation, we looked back at all cases of acute pancreatitis treated at Torbay Hospital in Torquay, UK, between January 1st, 2019, and December 31st, 2020. Those who were found to have chronic pancreatitis or whose baseline laboratory values could not be obtained were not includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Therefore, since these parameters used in daily practice are increased in many diseases, their use may not be safe in predicting severe pancreatitis, just like CRP, as seen in our results. [12,33–35]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, since these parameters used in daily practice are increased in many diseases, their use may not be safe in predicting severe pancreatitis, just like CRP, as seen in our results. [12,33–35]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since these parameters used in daily practice are increased in many diseases, their use may not be safe in predicting severe pancreatitis, just like CRP, as seen in our results. [12,[33][34][35] The main limitation of our study was its small sample size. No statistically significant differences were found between the mild and moderate pancreatitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…and for predicting organ failure, it was 4.88 [18]. Research by Halaseh et al [19] indicated that NLR could predict the severity of AP at initial diagnosis and might forecast adverse outcomes, the need for intensive care, and the length of hospital stay. These studies demonstrate that NLR is a useful biomarker for predicting the severity of acute pancreatitis early in the disease course.…”
Section: Plos Onementioning
confidence: 99%